METHODOLOGY OF THE IMPROVEMENT OF PRELIMINARY GIMNSTIC DISCIPLINES IN INCREASING ACTIVITY OF PRESCHOOL AGE CHILDREN (CASE OF UZBEKISTAN) - Tojiyevich, Khaydarov Baxtiyor; Xolboyevna, IbroimovaGulhayo; Baxtiyorovna, Tojieva Xolida (International Journal of Psychosocial Rehabilitation, 2020)
The article In training of physical education to enhanse activity of movement along with consolidation through preliminary gymnastic elements, in physical quality, to form fundamental movements and manner of development, to training motivation through child`rens age, gender chiefly their skills and qualification, their in order to enhanceiment discipline in base to organize preliminary gymnastic elements, to perform children`s vital necessary movement skill and qualification to oum in preschool.